Hubungan Self Efficacy dengan Self Care Management Hipertensi pada Lansia di UPT PSTW Jember - Kurdi, Fahruddin; Susumaningrum, Latifa Aini; Kusumadani, Fahra (Jurnal Kesehatan Komunitas, 2024)
Introduction: The increase in the number of cases of hypertension in the elderly is caused by the inability of the elderly to carry out self-care management of hypertension properly. This is influenced by the self-efficacy of the elderly to carry out self-care properly so that it can reduce the occurrence of complications of hypertension. Objective: to determine the relationship between self-efficacy and self-care management of hypertension in the elderly. Methods: This study used a correlational analytic design with a cross-sectional approach. Overall, the sample used was 35 hypertensive elderly at UPT PSTW Jember through a consecutive sampling technique. Data were analyzed using the Spearman-Rho test. Results: the study shows that the self-efficacy of the elderly has a mean value of 25 which can be interpreted as being in the moderate category. The majority of the elderly have hypertension self-care management in the moderate category (74%), good category (23%), and low category (3%). This study shows that there is a significant relationship between self-efficacy and self-care management of hypertension with a value of p = 0.001 <0.005 and a correlation coefficient with a positive value of 0.549. Conclusion: there is a significant relationship between self-efficacy and self-care management of hypertension in the elderly at UPT PSTW Jember, where the higher the self-efficacy of the elderly, the higher the self-care management of hypertension in the elderly. In this case, it is very important to increase the self-efficacy of the elderly at UPT PSTW Jember so that they have better self-care management.